Pemodelan Arsitektur Bisnis Pada Pelayanan Publik Polres Bojonegoro dengan Pendekatan Enterprise Architecture - Dea Ayu Permatasari; Aditya Rachmadi; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Polres Bojonegoro is part of an organization called the Indonesian national police (POLRI) based in district/city areas. The fundamental task force of the Polres Bojonegoro has been achieved in public service. To achieve integrated public service, Polres Bojonegoro should have a document that specifically explains the business infrastructure of the organization to Polres Bojonegoro at the moment. Therefore, Polres Bojonegoro will be more adaptive in addressing the changes that occur in organizations. So, modeling business architecture is done to develop business architecture in the Polres Bojonegoro using enterprise architecture approach. Business architecture requires an Open Group Architecture Framework (TOGAF), The method used by the researcher are TOGAF ADM (architecture development method). The research has blueprints describing the existing business architecture (baseline) and (target) for the public service of Polres Bojonegoro. The modelling of the public service business model for the Polres Bojonegoro has target the creation of the united public service of the Polres Bojonegoro via mobile app. Other than that, There is also a target to automatically do data input and data archive digitally. In this research, 5 gaps were found between the baseline and target of architecture models on public services Polres Bojonegoro, models of these architecture consists of references from preliminary, architecture vision, and business architecture.